SUBSURFACE DAMS TO HARVEST RAINWATER- A CASE STUDY OF THE SWARNAMUKHI RIVER BASIN, SOUTHERN INDIA - Raju N.Ja.; Reddy T.V.K.; Munirathnam P. (My University, 2006)
Declining water level trends and yields of wells, deterioration of groundwater quality and drying up of shallow wells are common in many parts of India. This is mainly attributed to the recurrence of drought years, over exploitation of groundwater, increase in the number of groundwater structures and explosion of population. In this subcontinent, the saving of water has to be done on the days it rains. India receives much of its rainfall in just 100 h in a year mostly during the monsoon period. If this water is not captured or stored, the rest of the year experiences a precarious situation manifest in water scarcity. The main objective behind the construction of subsurface dams in the Swarnamukhi River basin was to harvest the base flow infiltrating into sandy alluvium as waste to the sea and thereby to increase groundwater potential for meeting future water demands. An analysis of hydrographs of piezometers of four subsurface dams, monitored during October 2001–December 2002, reveals that there is an average rise of 1.44 m in post-monsoon and 1.80 m in the pre-monsoon period after the subsurface dams were constructed. Further, during the pre-monsoon month of June, much before construction of subsurface dams in October 2001, the water level was found fluctuating in the range of 3.1–10 m, in contrast to the fluctuation ranging from 0.4 to 3.1 m during the period following the construction of dams. Hence, the planning of rainwater harvesting structures entails thorough scientific investigations for identifying the most suitable locations for subsurface dams.
Keywords: RAINWATER HARVESTING; WATER RESOURCES; SUBSURFACE DAM; SWARNAMUKHI RIVER; GROUNDWATER LEVEL FLUCTUATIONS